Natchez Country : Indians, colonists, and the landscapes of race in French Louisiana - Milne, George Edward (Early American places, 2015)
"This manuscript focuses on the interactions between Native Americans and European colonists during the seventeenth and eighteenth centuries, particularly the relationships that developed between the French and the Natchez, Chickasaw, and Choctaw peoples. Milne's history of the Lower Mississippi Valley and its peoples provides the most comprehensive and detailed account of the Natchez in particular, from La Salle's first encounter with what would become Louisiana to the ultimate disappearance of the Natchez by the end of the 1730s. In crafting this narrative, George Milne also analyzes the ways in which French attitudes about race and slavery influenced native North American Indians in the vicinity of French colonial settlements on the Gulf coast, and how in turn Native Americans adopted and/or resisted colonial ideology"--